2001
DOI: 10.1046/j.1365-8711.2001.04594.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency variability and binarity of theδScuti star XX Pyx

Abstract: We analyse 147 h of single‐site CCD time series photometry of the multiperiodic low‐amplitude δ Scuti star XX Pyx with the aim of investigating variability at low frequencies. Part of the data were obtained in the context of the 1998 multisite campaign on XX Pyx, the results of which were described by Handler et al. We find that periodic low‐frequency variations are present in the XX Pyx light curves, and we detect two frequencies at fA=0.8695 cycle d−1 and fB=1.7352 cycle d−1, respectively, with amplitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…1 and de-noised following the method used for XX Pyx by Handler et al (2000), it is possibly caused by intrinsic low frequencies or binarity as shown by Arentoft et al (2001a). We have noted a similar sinusoidal amplitude variation appearing in the δ Sct star V1162 Ori (Arentoft et al 2001b), for which binarity (Arentoft & Sterken 2000) and multiperiodicity were proposed and well discussed.…”
mentioning
confidence: 56%
“…1 and de-noised following the method used for XX Pyx by Handler et al (2000), it is possibly caused by intrinsic low frequencies or binarity as shown by Arentoft et al (2001a). We have noted a similar sinusoidal amplitude variation appearing in the δ Sct star V1162 Ori (Arentoft et al 2001b), for which binarity (Arentoft & Sterken 2000) and multiperiodicity were proposed and well discussed.…”
mentioning
confidence: 56%
“…Handler et al (2000) found 22 independent Scuti frequencies in this A4 dwarf from an 81 day multisite photometric campaign; Arentoft, Sterken, & Handler (2001) found the low-frequency light variation, which they Fig. 6.-Computed radial-velocity curve of HD 207651 Aa compared with the six unit-weight observations.…”
Section: Discussionmentioning
confidence: 90%
“…Arentoft, Sterken & Handler (2001) shed new light on the nature of XX Pyx by suggesting the presence of a close companion. This hypothesis was based on two facts:…”
Section: Introductionmentioning
confidence: 99%
“…Arentoft et al (2001) concluded that XX Pyx may have a low‐mass companion and gave some preliminary constraints on its mass and the orbital inclination based on the velocity shift in the spectra published by Handler et al (1997).…”
Section: Introductionmentioning
confidence: 99%